Social Learning : Towards A Sustainable World (Wageningen Academic Publishers, 2007)
This book brings together a range of ideas, stories , and discussions about purposeful learning in communities aimed at creating a world that is more sustainable than the one currently in prospect. The book is designed to expand the network of conversations through which our society can confront various perspective, discover emerging patters, and apply learning to a variety of emotional and social contexts.